A comparison of self-nominated and actual speeds in work zones. (November 2015) - Debnath, Ashim Kumar; Blackman, Ross; Haworth, Narelle
Highlights: Literature lacks a scientific comparison of self-nominated and observed speeds in work zones. Drivers' self-nominated speeds are not valid indicators of their observed speeds. Young and middle-aged male drivers nominated higher speeds. Truck drivers nominated higher speeds than car drivers. Car drivers had larger differences in their self-nominated and observed speeds than truck drivers. Abstract: Despite significant research on drivers' speeding behavior in work zones, little is known about how well drivers' judgments of appropriate speeds match their actual speeds and what factors influence their judgments. This study aims to fill these two important gaps in the literature by comparing observed speeds in two work zones with drivers' self-nominated speeds for the same work zones. In an online survey, drivers nominated speeds for the two work zones based on photographs in which the actual posted speed limits were not revealed. A simultaneous equation modeling approach was employed to examine the effects of driver characteristics on their self-nominated speeds. The results showed that survey participants nominated lower speeds (corresponding to higher compliance rates) than those which were observed. Higher speeds were nominated by males than females, young and middle aged drivers than older drivers, and drivers with truck driving experience than those who drive only cars. Larger differences between nominated and observed speeds were found among car drivers than truck drivers. These differences suggest that self-nominated speeds might not be valid indicators of the observed work zone speeds and therefore should not be used as an alternative to observed speed data.